TANTANGAN DAN PELUANG PROGRAM STUDI BIMBINGAN DAN KONSELING ISLAM MENGHADAPI MASA DEPAN BANGSA (Jurnal Bimbingan dan Konseling Islam, 2013)
College is an educational institution that aims to produce graduates who are competent and ready to face the challenges and be able to take advantage of opportunities. BKI Studies Program has a mandate generate social and educational counselors are competent and excel. A number of challenges and opportunities faced by the academic community BKI Studies Program. All the challenges and opportunities need to be answered through the vision, mission and objectives and work plans BKI-directed study program. BKI Studies program also needs to prepare graduates for every candidate has a vision of life, a positive attitude, creative, adaptive, and intelligent hard work, focus, strong lifelong learning with a solid based spirituality.Keywords: self capacity, academic culture